Analysis of Reinforcement Connections in Columns with the Coupler Method in terms of Cost, Quality and Project Time the Stature - Achmad Murtadho; Kasimir Sawito; Abdul Mubarok; Edison Hatoguan Manurung; Sarjono Puro (PT FORMOSA CENDEKIA GLOBAL, 2023)
In selecting the type of material and the method of carrying out installation work on structural steel joints in the world of construction, things that must be considered in terms of cost, quality and time, there are two alternatives in selecting the type of reinforcement connection in column work, namely: lap splice and coupler, lap splice connection is a method traditional way to connect the two reinforcement when the column erection is carried out. Mechanical connection or (Coupler) is the newest method to connect two reinforcement using a coupler. The mechanical connection or connection (Coupler) does not depend on the strength of the concrete in the column, so this connection is stronger than the lapsplice connection. Data collection was carried out using the direct observation method in the field, and calculations were made on the column reinforcement joints with a tensile test (Coupler) to obtain 59.28 kgf/mm2 or 578.92 mpa. This refers to SNI-07-2052-2017 because in SNI the minimum limit for the tensile strength of reinforcing steel is 525 MPa. The calculation results show that reinforcement for 7 columns D32 with the Coupler method takes an average of 4221 minutes, or 9 days, 19 minutes/floor, and requires a total cost of 5449.50 minutes or 11 hours using the Lapsplice/overlap method. , 35 minutes/floor.